2021
DOI: 10.1042/bst20201231
|View full text |Cite
|
Sign up to set email alerts
|

Serpins in cartilage and osteoarthritis: what do we know?

Abstract: Serpins (serine proteinase inhibitors) are an ancient superfamily of structurally similar proteins, the majority of which use an elegant suicide inhibition mechanism to target serine proteinases. Despite likely evolving from a single common ancestor, the 36 human serpins have established roles regulating diverse biological processes, such as blood coagulation, embryonic development and extracellular matrix (ECM) turnover. Genetic mutations in serpin genes underpin a host of monogenic disorders — collectively t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 118 publications
(160 reference statements)
1
19
0
Order By: Relevance
“…The serpins are a superfamily of structurally similar proteins, the majority of which inhibit serine proteinases, and we have recently described their emerging role in cartilage [61]. In this study, we have identified remarkably high transcript expression levels of SERPINA1 gene in human cartilage.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The serpins are a superfamily of structurally similar proteins, the majority of which inhibit serine proteinases, and we have recently described their emerging role in cartilage [61]. In this study, we have identified remarkably high transcript expression levels of SERPINA1 gene in human cartilage.…”
Section: Discussionmentioning
confidence: 80%
“…Our study both supports and compliments these observations and provides novel insights into the proteolytic interplay between AAT, neutrophil elastase and MMP‐13, with potential consequences for the destruction of OA cartilage. AAT can have a role beyond proteinase inhibition [61] and the authors conclude that AAT was not only chondroprotective but also anti‐inflammatory and has a significant effect on pain [72]. This study and our own highlight the need to also investigate the effects of AAT administration using in vivo models of OA, with direct quantification of cartilage degradation, pain and inflammation.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, increased Col1a2 expression has previously been reported in osteoarthritic cartilage, in contrast to little or no expression in normal articular cartilage 35 . Serpine1 belongs to a family of serine proteinase inhibitors whose function, beyond inhibiting serine proteinases, is only recently emerging 36 . The role of Serpine1, that encodes for plasminogen activator inhibitor 1(PAI) in OA, is controversial since both increased and decreased expression have been reported in OA 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Serpine1 belongs to a family of serine proteinase inhibitors whose function, beyond inhibiting serine proteinases, is only recently emerging 36 . The role of Serpine1, that encodes for plasminogen activator inhibitor 1(PAI) in OA, is controversial since both increased and decreased expression have been reported in OA 36 . Some models suggest that osteoarthritic cartilage may lose the ability to produce protease inhibitors and that the subsequent imbalance between proteases and their inhibitors may contribute to chondropathy 37 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, obesity-induced biomechanical overload on joints results in periarticular trauma and joint deformity constituting the mechanical pathogenesis of KOA. Recent studies ( Wilkinson, 2021 ) have shown that genetic mutations in cartilage matrix proteins can induce the onset of KOA lesions. This suggests that KOA may be a hereditary disease in some cases.…”
Section: Introductionmentioning
confidence: 99%